New techniques for measurement and tracking of phase and frequency. - Hill, Martin T. (Curtin University, 1997)
This thesis presents and analyses new techniques to measure and track the phase and frequency of high frequency narrow bandwidth signals. In particular, these techniques are all digital in nature or can be implemented in digital integrated circuit technology.Presented first is a frequency measurement technique which involves sampling at regular intervals a binary quantized narrow band signal. The binary quantized samples are digitally processed to obtain the instantaneous frequency of the signal.It is shown that small phase movements in the signal can be detected even though the sampling occurs at a rate much lower than the signal frequency; that there are no frequency offsets in the frequency measurement technique; that the phase error in the technique is small and bounded provided the signal frequency is maintained within derived limits. Other properties of the technique are also derived.The frequency measurement technique is experimentally demonstrated in a number of typical applications.Secondly, a new phase tracking system is presented, which has similarities to conventional phase locked loops. However, unlike phase locked loops, the new system incorporates a local reference source which effectively stabilizes the phase estimate of the signal input being tracked.It is shown that the new system has the following advantages: Precise centre frequency, controllable lock range, and elimination or reduction of the effects of imperfections like voltage controlled oscillator phase noise. General behaviour in noise of the new phase tracking system is derived.An implementation of the new system is presented which employs the frequency measurement technique described above. This implementation is characterized by very precise centre frequency, high phase noise suppression, and can be built almost entirely in digital integrated circuit technology. The new system is experimentally demonstrated in some typical applications.The techniques presented in this thesis provide improvements of several orders of magnitude in the ability of systems implemented in digital integrated circuit technology to: Measure and control phase and frequency of narrow band signals; Implement high performance phase tracking systems.